The ewe of Ghana and Togo on the eve of colonialism : a contribution to the Marxist debate on pre-capitalist socio-economic formations. - Asamoa, Ansa K. (Tema : Ghana Publishing Corporation, 1986)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: marxisme; sociale economie; Ghana; Togo